Radiation dose among different cardiac and vascular invasive procedures: The RODEO study. (1st August 2017) - Sciahbasi, Alessandro; Ferrante, Giuseppe; Fischetti, Dionigi; Miklin, Daniel Jonathan; Sarandrea, Alessandro; Schirripa, Valentina; Guarracini, Fabrizio; Arya, Arash; Loreni, Giorgio; Bruni, Antonio; Rigattieri, Stefano; Marini, Massimiliano; et al.
Abstract: Background: Interventional radiology and cardiology procedures contribute significantly to the collective dose of radiation exposure from medical interventions. Recent and dedicated studies comparing directly these procedures in term of patient radiation exposure are lacking. Our aim was to compare radiation exposure among different interventional procedures performed under fluoroscopic guidance. Methods: The RODEO study (NCT: 02972736) is an international observational retrospective multicenter study enrolling all patients undergoing diagnostic or interventional procedures performed by different interventional operators (i.e. radiologists, interventional cardiologists or electrophysiologists) in 6 centers, without exclusion criteria. The primary end-point of the study was the comparison of dose area product (DAP) among interventional cardiology, electrophysiology or interventional radiology procedures. Results: A total of 17, 711 procedures were included in the study: 13, 522 interventional cardiology, 2352 electrophysiology and 1864 interventional radiology procedures. The highest DAP values were observed for interventional radiology procedures (74 Gy ∗ cm 2 [Interquartile range 27–178 Gy ∗ cm 2 ]), followed by interventional cardiology (40 Gy ∗ cm 2 [22–78 Gy ∗ cm 2 ]) and electrophysiology procedures (13 Gy ∗ cm 2 [4–44 Gy ∗ cm 2 ], p < 0.0001). In term of specific procedures, the highest DAP values were observed in structural or valvular cardiac procedures (134 Gy ∗ cm 2 [51–260 Gy ∗ cm 2 ]) whereas the lowest DAP values in pacemaker insertion (11 Gy ∗ cm 2 [4–28 Gy ∗ cm 2 ]). Conclusion: In this large multicenter study, the highest radiation exposure was observed in procedures performed by interventional radiologists. However, among specific procedures, structural or valvular cardiac procedures were associated with the highest radiation exposure.